-5p=5(6+p)+3p

Simple and best practice solution for -5p=5(6+p)+3p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5p=5(6+p)+3p equation:



-5p=5(6+p)+3p
We move all terms to the left:
-5p-(5(6+p)+3p)=0
We add all the numbers together, and all the variables
-5p-(5(p+6)+3p)=0
We calculate terms in parentheses: -(5(p+6)+3p), so:
5(p+6)+3p
We add all the numbers together, and all the variables
3p+5(p+6)
We multiply parentheses
3p+5p+30
We add all the numbers together, and all the variables
8p+30
Back to the equation:
-(8p+30)
We get rid of parentheses
-5p-8p-30=0
We add all the numbers together, and all the variables
-13p-30=0
We move all terms containing p to the left, all other terms to the right
-13p=30
p=30/-13
p=-2+4/13

See similar equations:

| 4(5x+1)=(1/2)(20x+16)+16 | | 39-3b=-7(8b+2) | | 4n-2=-2+8n | | 3/4x+9=24 | | 700-20w=450 | | n+1-3n=9-n | | (x/5)+6.2=-6.3 | | 2v+9=8v+22 | | 2x+20+2x+4=180 | | P+1=8p+6 | | -11b=90=-2b | | 8x+x=7x+13 | | -5(2x+9)=5x | | 5x+23x-1=7(4x+9) | | 64s2+144s=-81 | | 2x+4x+3x=64 | | 7=-5-(-w) | | 2/3(t+6)-1/4(4-3t)=5/6(t+3)+1/2(t+2) | | 3x+15-9x=105 | | -4x-x+30=0 | | 6y+6(-4+4y)=126 | | (X-2y)=(3y-X) | | 3n+2n=29 | | X^=y^+16 | | 33+c=13c+16-20 | | 7/y-2=-2 | | X^=y | | 9z-8=5z+23 | | 1,7=x+0,1 | | 25=y/5-17 | | 4q​=3 | | 4b+16=5b |

Equations solver categories